Innovative complex correction of poststress disorders - I. А. Bokova; L. G. Agasarov (Лечащий Врач, 2021)
In the paper, the options of post-stress violations in persons of dangerous professions (law enforcement officers, participants in the aftermath of the Chernobyl disaster) are detailed and on this basis adequate ways of correcting these shifts are substantiated. In a study of 1,250 men associated with stress-activity, 490 individuals were selected for infused neuropsychiatry and cardio-vascular disorders. Taking into account the tasks, the mental status and condition of the cardiovascular system of patients were assessed. Originally (in addition to medical treatment) in the course of comparing the effectiveness of respiratory-relaxation training and autogenic training were noted the benefits of the first. These data identified the need to use, along with psychotherapy, a method of pulsogeoindication, which proved to be in the correction of both neurotic and somatic disorders. The proposed complex of psychocorrection and pulsogemoindication slightly increased the effectiveness of treatment of participants in local middle-aged operations. On the other hand, it was reliably more effective than the comparable approaches in older persons – both liquidators and veterans of law enforcement agencies. On the other hand, catamnestic analysis reflected the great therapeutic reliability of the complex in relation to participants in local operations. In general, the results of the study allow to consider pulsogeoindication as an effective component of rehabilitation of persons associated with stress.